2003
DOI: 10.1190/1.1581036
|View full text |Cite
|
Sign up to set email alerts
|

Processing, inversion, and interpretation of a 2D seismic data set from the North Viking Graben, North Sea

Abstract: Simultaneous elastic impedance inversion is performed on the 2D North Viking Graben seismic data set used at the 1994 SEG workshop on amplitude variation with offset and inversion. P‐velocity (Vp), S‐velocity (Vs), density logs, and seismic data are input to the inversion. The inverted P‐impedance and S‐impedance sections are used to generate an approximate compressional‐to‐shear velocity ratio (Vp/Vs) section which, in turn, is used along with water‐filled porosity (Swv) derived from the logs from two wells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…For a fixed lithology and porosity, V p /V s is 10% -20% lower for gas saturation than for water saturation, but there is some overlap in V p /V s ratio between brine sands and oil sands. Shales have higher V p /V s values than sands [6]. For water saturated and gas saturated sediments, the V p /V s ratio increases with increasing porosity, and also showed that V p /V s could effectively be used to separate water saturated and gas saturated sediments as porosity increases.…”
Section: Inversionmentioning
confidence: 92%
See 1 more Smart Citation
“…For a fixed lithology and porosity, V p /V s is 10% -20% lower for gas saturation than for water saturation, but there is some overlap in V p /V s ratio between brine sands and oil sands. Shales have higher V p /V s values than sands [6]. For water saturated and gas saturated sediments, the V p /V s ratio increases with increasing porosity, and also showed that V p /V s could effectively be used to separate water saturated and gas saturated sediments as porosity increases.…”
Section: Inversionmentioning
confidence: 92%
“…Ambiguities in lithology and fluid identification based only on the P-impedance can often be effectively removed by adding information about V p /V s related attributes at non normal incidence as described by [6]. The V p /V s ratio is a useful discriminant of lithologies and fluid content.…”
Section: Inversionmentioning
confidence: 99%
“…To strengthen the conclusions from the interpretation of the seismic image shown in Figure 10, we chose three trace corresponding to CMPs 700, 1100, and 1500. Figure 11 depicts a remarkable amplitude gain and resolution of the Q-compensated seismic traces, mainly in the region where sand and intense fracturing gas is present (Keys and Foster, 1994;Madiba and McMechan, 2003).…”
Section: Distance (Km)mentioning
confidence: 96%
“…Thus, it is difficult to delineate hydrocarbon reservoirs directly on the separate inverted P-impedanceand S-impedancesections. Ambiguities in lithologic and fluid identification based only on the acoustic impedance can often be effectively removed by adding information about V p /V s related attributes at nonnormal incidence [22,23,24,25].…”
Section: Figure 6 P-impedance Versus S-impedance Crossplot Showing Mmentioning
confidence: 99%